The last forty years of landscape design and planning: (1984-2024) - Balogh , Péter István; Szabó, Gábor; Szabadics, Anita; Auer, Jolán (4D Journal of Landscape Architecture and Garden Art, 2024)
The chapter discusses the distinct branches of landscape architecture: landscape design of gardens, parks, urban open spaces, design of registered historic gardens, landscape planning, planning of local green space networks and spatial planning. Landscape design and planning, like architecture, responds to and is fundamentally dependent on the needs and expectations of society. It is therefore important to outline the main social processes of the last forty years.The chapter focuses on the landscape projects realised rather than on the plans, since it is the result of the design process, the completed project, that is most important. It tells us almost everything, about the times in which it was conceived and in which the designer, the client, the constructor and the users existed. The results and social impact of landscape design can be seen mainly in the completed work. There is usually a narrow professional interest in the plans that remain in the drawer.The results of landscape planning and green space planning at local level and spatial planning are only visible many years later, making it more difficult to follow the social impact. Therefore, in the case of landscape planning and green space planning at local and regional level, the chapter is limited to outlining only the trends over four decades.
Keywords: landscape architecture; planning